Are private banks more efficient than public banks? Evidence from Russia - Alexei Karas; Koen Schoors; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
We study whether bank efficiency is related to bank ownership in Russia. We find that foreign banks are more efficient than domestic private banks and - surprisingly - that domes-tic private banks are not more efficient than domestic public banks. These results are not driven by the choice of production process, the bank's environment, management's risk preferences. the bank's activity mix or size, or the econometric approach. The evidence in fnicl suggests that domestic public banks arc more efficient than domestic private banks and that the efficiency gap between these two ownership types did not narrow after the introduction of deposit insurance in 2004. This may be due to increased switching costs or to the moral hazard effects of deposit insurance. The policy conclusion is that the efficiency of the Russian banking system may benefit more from increased levels of competition and greater access of foreign banks than from bank privatization.
URN:NBN:fi:bof-201408071898
Keywords: G21; P30; P34; P52; 330; Bank efficiency; state ownership; foreign ownership; Russia